Managing Metastatic Thymoma With Metabolic and Medical Therapy: A Case Report - Phillips, Matthew C. L.; Murtagh, Deborah K. J.; Sinha, Sanjay K.; Moon, Ben G. (Frontiers in Oncology, 2020)
Thymomas consist of neoplastic thymic cells intermixed with variable numbers of non-neoplastic lymphocytes. Metastatic thymomas are typically managed with chemotherapy to control tumour-related symptoms; no prolonged survival is expected. Metabolic-based approaches, such as fasting and ketogenic diets, target cancer cell metabolism by creating an increased reliance on ketones while decreasing glucose, glutamine, and growth factor availability, theoretically depriving cancer cells of their metabolic fuels while creating an unfavourable environment for cancer growth. This may be beneficial in metastatic thymoma. We report the case of a 37-year-old woman with myasthenia gravis, diagnosed with an inoperable type AB, stage IVA thymoma, who pursued a metabolic intervention consisting of periodic fasting (seven-day, fluid-only fasts every one to two months) combined with a modified ketogenic diet on feeding days. She managed her metastatic thymoma for two years with this approach, remaining active and maintaining her body weight. Fasting-related adverse effects included cold intolerance, fatigue, and generalized muscle aches, which all resolved during the second year. She experienced two myasthenia relapses, each associated with profoundly reduced oral intake, marked weight loss, and tumour regression - the first with 6 kg weight loss and a 32% decrease in tumour volume over four months, the second with 15 kg weight loss and a 96% decrease in tumour volume over four months. Prednisone was required for myasthenia control during the second relapse. This case is unique in that a combined metabolic and medical approach produced a near-complete regression of a metastatic thymoma in the absence of surgery, chemotherapy, or radiotherapy. Nearly three years after being diagnosed with a metastatic cancer, our patient continues her metabolic therapy, shows no signs of disease, and leads a full and active life. Although we cannot be certain of the mechanism underlying this remarkable outcome, we hypothesize that two years of periodic fasting combined with a ketogenic diet metabolically weakened the neoplastic thymic cell component of the thymoma, “setting the stage” for immune activation and extreme calorie restriction to destroy most of the cancer cells during both relapses, while prednisone-induced apoptosis eradicated the remaining lymphocytic component of the thymoma during the second relapse.